Prevention and control of COVID-19 in pastoral community through One Health Approach - Yousuf, Abdilahi; Mohd Arifin, Siti Roshaidai; Musa, Ramli; Md Isa, Muhammad Lokman (Elsevier B.V., 2020)
The vast majority of its population being a pastoralist community, the Somali region in Ethiopia shares the longest border with its neighboring east African countries. These communities face a high risk for transmission of imported COVID-19 cases and remain vulnerable due to lack of access to health delivery and low utilisation of services. Valuable lessons from other countries, has placed the One Health Approach as an appropriate, feasible and applicable preventive and control measure for COVID-19. This paper discusses the epidemiological and social susceptibility of pastoral communities in the transmission of COVID-19 and the introduction of One Health Approach as an effective inter-disciplinary response and management.